Adaptive Datagram Transport Protocol Over Ad-hoc Network – TCP Fairness - Senthil Kumaran, M (International Journal of Computer Sciences and Engineering, 2025)
High-speed and satellite networks are emerging fast in the communication domain. Bandwidth Delay Products (BDP) plays an important role in the design of a congestion control algorithm for the effective usage of network resources. Bandwidth-delay products (BDPs) are referred as the maximum amount of unacknowledged data that allowed in flight at any moment in the network. TCP is originally designed for a general wired network. In case of BDP, packet losses rarely occur. TCP can no longer guarantee good bandwidth utilization. For MANETs having extremely small BDPs and frequent packet losses cannot use the existing transport protocol. Numerous solutions proposed to provide reliable packet delivery in MANETs in recent years. Solutions proposed to provide reliable packet delivery in MANETs are non-TCP variants and TCP variants. Non-TCP variants focus on the modification of congestion control algorithms in the transport protocol. It requires complicated mathematical computation and incur excessive network overhead. Although relatively accurate congestion information obtained, it cannot retain the end-to-end semantics of a transport protocol. TCP variants adopts Additive Increase Multiplicative Decrease (AIMD) congestion control algorithm with unnecessary large transmission windows. The proposed model develops an improved Datagram Transport Protocol over Ad Hoc Networks (DTPA) for MANETs. The improvement is carried out in the direction of achieving fairness in the TCP flow of the MANET. Adaptive Max-Min Fairness algorithm is deployed in the proposed DTPA improvement. The proposal work provides an effective datagram-oriented end-to-end reliable transport protocol DTPA (Datagram Transport Protocol over Ad Hoc Networks) incorporating, a fixed-size window- based flow-control algorithm and a cumulative bit-vector-based SACK (selective ACK) strategy. The proposal also guarantees reliable transmission and recovering packet losses. It improves the network performance in terms of throughput, round-trip time, number of retransmissions, and IP queue size demonstrated by simulation conducted using NS2.